Legal Education and Tuition in the Civil Society as the Most Important Condition of Harmonization of International Relations - Ghazinyan , G. (Bulletin of Yerevan University C: Jurisprudence, 2016)
Law is an integrating factor of the civil society, and its members should be first of all legal personalities. Other characteristics of the members of the civil society (profession, nationality, etc.) are not inherent. The main problem of the modern Armenian and other post soviet societies is the crisis of legality and legal order. Deep roots of this crisis are in the low level of legal awareness and legal culture peculiar to the population. One of the main methods to overcome the legal nihilism is the introduction of the system of civil and state legal education and tuition. These axiomatic provisions must be used both in the legal regulation of establishment and activity of educational institutions, and in their local normative regulation. As a result - the main goal of these educational institutions should be formation of a person with legal culture, and the way to reach this goal is general legal tuition and education as an essential element of general and professional education.
Keywords: civil society, legal personality, legal nihilism, legal education and tuition